Understanding inequality in Brazil: A conceptual overview - François Bourguignon; Francisco de Hollanda Guimar\~aes Ferreira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
This is a background note to a joint IPEA/World Bank Report, provisionally entitled "Selected Topics on Income Inequality in Brazil", with publication planned for 2001. The purpose of the note is twofold. First we propose four central questions which the Report should seek to address, and around which it can be structured. These are: "What is unique about Brazil's inequality?"; "Why does inequality matter?"; "Which inequality matters most?"; and "What - if anything - can the government do about it?". Second, we provide reasonably detailed outlines for four background papers for the Main Report: each addressing one of the foregoing questions.
Keywords: D63; I38; 330